PREPARATION AND CHARACTERIZATION THE NON-SULFIDED METAL CATALYST: Ni/USY and NiMo/USY - Khoirina Dwi Nugrahaningtyas; Wega Trisunaryanti; Triyono Triyono; Nuryono Nuryono; Dian Maruto Widjonarko; Ari Yusnani; Mulyani Mulyani (Indonesian Journal of Chemistry, 2009)
The two-new catalysts had been prepared by using the impregnation method according to Nugrahaningtyas [6] and Li [4]. One catalyst is of Nickel (Ni), supported on Ultra Stable Zeolite Y (USY), whereas the other one is NiMo supported on same supporting agent. These new catalysts are expected to be more effective when applied on the hydrotreatment reaction in standpoint of its capabilities on removing the unwanted-heteroatom. Characterization those two types of catalysts then carried out by using the criteria of acidity, porosity and, metal content. The result shows that these non-sulfide catalysts have several good characters that supporting their usefulness in hydrotreatment-catalytic reaction. In addition, catalyst NiMo/USY - 1 performs many ideal criteria as the best functional catalyst.